2016
DOI: 10.21273/jashs.141.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Tolerance Attributes during Spring Deacclimation for Three Asparagus Cultivars with Varying Adaptation to Southern Ontario

Abstract: Winterhardiness in asparagus (Asparagus officinalis) may be related to proper cold acclimation and induction of freezing tolerance in the fall, levels and maintenance of freezing tolerance in the winter, and the timing of deacclimation in the spring. Premature deacclimation and the inability to reacclimate could result in crown damage from spring freeze-thaw cycles. A field experiment was conducted, replicated over 2 years, to determine how three cultivars with varying adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Although there is no consensus regarding the relationship between the plant tissue water content and cold hardiness, most researchers believe that cold hardiness is negatively associated with increasing water content due to lower water content can decreased osmotic pressure 5 , 7 , 8 , 42 . In this study, an analysis of acclimation revealed that the freezing tolerance of alfalfa was highest in phase 3 because of its decreased water content and freezing conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no consensus regarding the relationship between the plant tissue water content and cold hardiness, most researchers believe that cold hardiness is negatively associated with increasing water content due to lower water content can decreased osmotic pressure 5 , 7 , 8 , 42 . In this study, an analysis of acclimation revealed that the freezing tolerance of alfalfa was highest in phase 3 because of its decreased water content and freezing conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A series of physiological, biochemical, and molecular changes induced by photoperiod and temperature maximize the freezing tolerance of plants during acclimation 3 5 . Earlier research indicated that the hardiness of perennial ryegrass ( Lolium perenne L.) 6 and asparagus ( Asparagus officinalis L.) 7 , 8 is negatively associated with increasing water contents. A decrease in the water content can lower the freezing point of cells, whereas an increase in the water content may result in mechanical damages due to extracellular freezing as well as an increase in the ice propagation rate in tissues 7 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrates not only act as osmotic regulators to protect the integrity of cell structure and function, but are also intracellular signaling molecules that regulate gene expression during plant growth and development, and are strongly associated with plant cold resistance [45,46]. Increase in the contents of total soluble sugars, sucrose, glucose, fructose, and trehalose in cells is beneficial to improve the cold resistance of plants [8,45,47,48]. In the current study, surface drip irrigation (Deep-0) was more conducive to accumulation of soluble sugars, sucrose, glucose, and fructose in the root crown, whereas trehalose content showed no significant difference among the treatments, which was consistent with the trend in change of LT 50 .…”
Section: Discussionmentioning
confidence: 99%